Development of a statistical evaluation model, to reduce accident rates at the Uchucchacua Mine - Rodríguez Vigo, Carlos Enrique (2020)
This investigation allowed to evaluate the results of risk management in a mining operation. This highlights the importance of adopting preventive measures to control the causes of accidents. To this end, a methodology is developed that allows identifying and giving maximum attention to the existing critical risks, determined from evaluating and analyzing the information provided in the Accident Investigation Reports. Thus, the predominant work characteristics are recognized in the occurrence of accidents, to systematically address them and avoid the damage they generate. This methodology uses the Pareto Principle, to find in a practical way, those few characteristics of the work that still influence the accident rate, in which we must focus our management as a priority. It also allows identifying the ‘target audience’ that is the most affected by the damage. All this properly managed information can facilitate acting preventively to control risks at work, seeking to protect staff and avoid new or repetitive events that affect them.